Інформаційна технологія контролю шкідливих викидів енергоактивних об'єктів - Нога, Андріан Юрійович (Національний університет "Львівська політехніка", 2015)
У дисертаційній роботі розв’язано актуальну науково-практичну задачу розроблення науково-практичної технології відбору даних про концентрацію шкідливих викидів продуктів згорання в котлі енергоблоку та підвищення ефективності управління. Проведено аналіз структури енергоблоку, показано що він має агрегатну, ієрархічну структуру та обґрунтовано вибір математичного апарату для аналізу динаміки та інформаційних технологій відбору і опрацюванню даних про хімічну структуру продуктів згоряння палива і їх концентрації. Розроблено процедуру побудови структури інформаційно-логічної моделі процесу кризового управління; показано, що для якісного управління необхідно використовувати логічні й системні моделі відображення ситуацій для прийняття рішень на антикризове управління з урахуванням причинних зв’язків впливу факторів. Розроблено модель і обґрунтовано інформаційну структуру системи відбору і опрацювання даних про шкідливі викиди продуктів згоряння як компоненти АСУ–ТП та експертної системи. Розроблено структурно-інформаційну схему енергоблоку, показано, що вона забезпечує адекватне відображення ситуації в ТЕС і є основною побудови причинно-наслідкових графів для інформаційно-ресурсних потоків в енергоблоках, що дало змогу моделювання динаміки та прогнозу ситуацій. В диссертационной работе решено актуальную научно-практическую задачу разработки научно-практической технологии отбора данных о концентрации вредных выбросов продуктов сгорания в котле энергоблока и повышения эффективности управления. Проведен анализ структуры энергоблока, показано, что он имеет агрегатную, иерархическую структуру и обоснован выбор математического аппарата для анализа динамики и информационных технологий отбора и обработки данных о химической структуре продуктов сгорания топлива и их концентрации. Разработана процедура построения структуры информационно-логической модели процесса кризисного управления; показано, что для качественного управления необходимо использовать логические и системные модели отображения ситуаций для принятия решений на антикризисное управление с учетом причинных связей влияния факторов. Разработана модель и обосновано информационную структуру системы отбора и обработки данных о вредных выбросах продуктов сгорания как компоненты АСУ-ТП и экспертной системы. Разработано структурно-информационную схему энергоблока, показано, что она обеспечивает адекватное отображение ситуации в ТЭС и является основной построения причинно-следственных графов для информационно-ресурсных потоков в энергоблоках, что позволило моделировать динамику и прогнозировать ситуации. The thesis solved current scientific and practical problem of developing scientific and practical technology of selection of data on the concentration of harmful products of combustion in the boiler of a power unit and of improving control. Analysis of the structure of power unit was conducted, it was shown that the power unit has aggregate, hierarchical structure, and the choice of mathematical tools to analyze the dynamics and information technology for selection and processing of data on the chemical structure of the combustion products and their concentration was proven. The procedure of constructing the structure of the information and logical model of the crisis management process was elaborated; it was shown that for qualitative control logic and system models of displaying of situations to make decisions for anti-crisis management based on causal relationships of the influence factors must be used. A model was created and information structure of the selection and processing of data on emissions of combustion products as components of ACS - TP and expert system was substantiated. A structural informational scheme of power unit was elaborated, it was shown that the scheme provides an adequate reflection of the situation in TPP and serves as the basis for construction of cause-and-effect graphs for information and resource flows in the power units, which enabled the modeling of dynamics and prediction of situations. The analysis of the ability of the operator to meet decisions and shape the flow of control of the power unit in normal, marginal and emergency modes was conducted. It was shown that psychological and intellectual readiness to risk and the adequacy of behavior in the marginal and emergency power unit work modes, mobilizes the intellectual resources of the operator. He works out the ability to recognize the nature of failures in the system and instant recovery of scenarios from memory of cause-andeffect relationships to identify defects and meet appropriate decisions for their elimination. The analysis of the information components of decision-making process based on data from ACS – TP and additional data from the emissions control system (ECS) with remote transmission of measurement results was conducted. The strategy of decision forming and decision making and their step-by-step introduction, the development of schemes of behavioral actions under the concept by Anokhin was proven. The concept of operational provisioning of the database in real-time mode was substantiated and hierarchical scheme of forming of control actions by a complex object (power unit) was proven. A choice and the substantiation of the structure of information - measuring system (ECS) to control emissions of combustion products of fuel in the boiler of the power unit and a plan for installation of sensors of ECS according to the scheme was made.
Информационная технология контроля вредных выбросов энергоактивных объектов
Information technology of emission control for power objects
Keywords: енергоблок; ієрархічна структура; експертна система; причинно-наслідковий граф; энергоблок; иерархическая структура; экспертная система; причинно-следственная граф; power unit; hierarchical structure; expert system; cause-and-effect graph